High strain rate characterization of polymers - Siviour, CR (AIP Publishing, 2017)
This paper reviews the literature on the response of polymers to high strain rate deformation. The main focus is on the experimental techniques used to characterize this response. The paper includes a small number of examples as well as references to experimental data over a wide range of rates, which illustrate the key features of rate dependence in these materials; however this is by no means an exhaustive list. The aim of the paper is to give the reader unfamiliar with the subject an overview of the techniques available with sufficient references from which further information can be obtained. In addition to the ‘well established’ techniques of the Hopkinson bar, Taylor Impact and Transverse impact, a discussion of the use of time-temperature superposition in interpreting and experimentally replicating high rate response is given, as is a description of new techniques in which mechanical parameters are derived by directly measuring wave propagation in specimens; these are particularly appropriate for polymers with low wave speeds. The vast topic of constitutive modelling is deliberately excluded from this review.